CULTURAL IDENTITY CONSTRUCTION IN THE NOVEL 'EAST WIND: WEST WIND' BY PEARL S. BUCK - Neisya Neisya; Puspa Lutpiyana Duwi Lestari; Fitria Aprilia (UIN Raden Mas Said Surakarta, 2022)
This study analyzed the cultural identity in the novel East Wind: West Wind written by Pearl S. Buck by using postcolonial theory proposed by Bhabha (2007). It aimed to identify the cultural identity, that consists of stereotypes, mimicry, ambivalence, and hybridity, and how it was experienced by the main character in the novel. This study used qualitative method with descriptive approach. The writer collected the data by reading the novel and highlighting the data from the narrations and utterances that were appropriate to the problem of study. The result of this study showed that there are cultural identity construction in the life of Kwei-lan’s, the main character in the novel, which trapped her into identity confusion. Two cultures, namely traditional Chinese and Western culture, cause Kwei-lan’s confusion of her identity. Kwei-lan's attempts to survive from this situation by imitating the modern lifestyle, such as habits, appearances, and parental actions. This cultural shift makes her feel uncanny or being in an unhomely moment where she sticks in the middle between past and present, or between her origin Chinese culture and her new modern Western life.